Limitations and opportunities of smallholders’ practical knowledge when dealing with pig health issues in northern Uganda - Arvidsson, Anna; Fischer, Klara; Chenais, Erika; Kiguli, Juliet; Sternberg-Lewerin, Susanna; Ståhl, Karl (Public Library of Science, 2023)
Pig production has a short history in Uganda. The majority of pigs are kept by smallholder farmers in rural areas where access to veterinary services is limited, and pig keeping has been suggested as a potential pathway out of poverty for smallholders. Previous research has identified the disease of African swine fever (ASF) as a major threat, causing high mortalities in pigs. With no available cure or vaccine, the only option is to implement biosecurity measures, i.e. strategies that prevent the spread of ASF. This paper draws on data from four months of ethnographic fieldwork in rural northern Uganda. Combining methods of participant observation, semi-structured interviews, focus group discussions and a survey, the aim was to improve understanding of smallholders’ perceptions and responses to pig health issues such as ASF. Applying the concept of practical knowledge, this paper analyses the potential and limitations of smallholders’ practice-based knowledge as a means of dealing with pig health issues. The results show that while pigs were appreciated locally for providing an income, many informants found it difficult to deal with pig diseases effectively. Consequently, informants commonly expressed a need for other kinds of knowledge in their pig production, indicating that veterinary advice can play an important role in reducing the negative impact of pig health issues. For animal health provision to have relevance in this context, however, veterinary practitioners must pay close attention to smallholders’ priorities and ways of knowing in their livestock keeping. Results further show that pig health issues made some informants abandon pig production altogether. To enhance the potential of pig production as a poverty mitigation strategy in Uganda, research and policy need to focus on ways of bettering general conditions for smallholder pig keeping, including improving the quality of and access to veterinary services in rural areas.